Q. 1 C

# Solve the followi

Answer :

Multiply the first equation by b

⇒ bx + by = ab + b^{2} …[1]

⇒ ax — by = a^{2} — b^{2} …[2]

Now, eq[2] + eq[1]

x(a + b) = a^{2} + ab

⇒ x(a + b) = a(a + b)

⇒ x = a

by x + y = a + b and x = a

x + y = a + b (x = a)

⇒ y = b

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Introduction to Linear Equations in Two Variables62 mins

Revision on Substitution and Elimination Method44 mins

Revision on Word Problems - 150 mins

Revision on Word Problems - 235 mins

Two Stories about Flying39 mins

Resistors in Parallel39 mins

Transportation in One Shot42 mins

Resistors in Series42 mins

Human Reproduction in One Shot45 mins

Reflection of light-238 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Solve the followiGujarat Board Mathematics

The sum of the diGujarat Board Mathematics

Solve the followiGujarat Board Mathematics

By cross multipliGujarat Board Mathematics

In AABC, the measGujarat Board Mathematics

Solve the followiGujarat Board Mathematics

Solve the followiGujarat Board Mathematics

Solve the followiGujarat Board Mathematics

An employee deposGujarat Board Mathematics

The sum of presenGujarat Board Mathematics